Pediatric Fulminant Hepatic Failure: Insights from a Tertiary Care Hospital in Pakistan on Etiology, Clinical Presentation, and Prognosis - Abdul Qadir, Muhammad Hanif, Ibrahim, Mahesh Kumar Luhano, Zarmast Khan, Fayaz Ahmed Memon (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to examine the causes, clinical manifestations, and outcomes of fulminant hepatic failure in children treated at a tertiary care facility in Pakistan. Study Design: Retrospective/observational study Place and Duration: Deapartment of Pediatrics, LMC, Loralai Medical College Loralai, Balochistan in the duration from May, 2022 to October, 2022. Methods: Total 66 children of age 1 months to 14 years with fulminant hepatic failure were included in this study. Case enrollment included collecting thorough demographic information after receiving informed written consent. Acute liver failure (INR>2.0) with or without hepatic encephalopathy within 8 weeks of the beginning of clinical liver illness was considered to be indicative of FHF. SPSS 20.0 was used to analyze all data. Results: Mean age of the children was 5.8±7.26 years. There were majority 42 (63.6%) males and 24 (36.4%) females among all cases. Most common etiology was infection found in 35 (53.03%) cases followed by drug induced, autoimmune hepatitis, undetermined etiology and metabolic etiology. As per lab findings, mean bilirubin of the patients was 22.3±6.30 mg/dl, mean ALT was 1106.2±4.88 U/L, mean AST was 1495.11±6.90 U/L and mean INR was 5.2±3.14. Outcomes were good, 51 (77.3%) patients were discharged and 15 (22.7%) patients were died. Conclusion: The study shows that viral infections are the main cause of severe liver failure in kids. We found that infant and child mortality rates were low. Keywords: Pediatric fulminant hepatic failure, Clinical spectrum, Etiology